Vidi del buon Signor l'anima forte! : portréty Diega d'Aragona Pignatelliho od Franceska Solimeny a jeho dílny - Kazlepka, Zdeněk (2019)
In the castle in Jindřichův Hradec there is a large portrait of Don Diego d'Aragona Pignatelli, Duke of Terranova and Monteleone (1687–1750), which in this article we ascribe to the artist Francesco Solimena (1657–1747). There are multiple versions of this painting, all of which are based on an oil sketch that is now in the collection of the Metropolitan Museum in New York. Solimena painted the portrait of Diego Pignatelli, a close friend of Charles VI, at least one other time, evidence of which is provided by another oil sketch, this one located in the Hermitage in Saint Petersburg. In the latter portrait Pignatelli is depicted wearing the uniform of a general in the Neapolitan Cavalry. Both portraits, which we can assign to a category of work know as 'status portraits' ('ritratto di stato'), date from the early thirties, around the years 1732–1734.